RELASI ANTARA TEOLOGI BIBLIKA DENGAN TEOLOGI SISTEMATIKA - Suparna (STT BIBLIKA JAKARTA, 2024)
Biblical theology and systematic theology are two sciences that are equally important in the world of theology. However, not everyone knows what the real relationship between biblical theology and systematic theology itself is. The aim of this research is to investigate the relationship between biblical theology and systematic theology. This research uses qualitative research methods with literature study. Based on the research conducted, the conclusion is that in dialogical interactions systematic theology can help biblical theology.